Retrospective Analysis of Total Laparoscopic Hysterectomy Experience in a Single Center for Five Years - Özcan, Hüseyin Çağlayan; Uğur, Mete Gürol; Sucu, Seyhun; Bayramoğlu Tepe, Neslihan; Kömürcü Karuserci, Özge; Güneyligil Kazaz, Tanyeli (European Journal of Therapeutics, 2023)
Objective: To analyze the indications, complications, and clinical outcomes of total laparoscopic hysterectomies (LH) for benign diseases in a tertiary health care hospital over a period of five years. Methods: This retrospective cohort study includes 151 patients that underwent total laparoscopic hysterectomy (TLH) for benign indications at a university hospital between 2013 and 2017. Results: Abnormal uterine bleeding (44.4%) was the most common indication. The mean hospital stay, estimated blood loss, and operative time were 2.3±1.2 days, 159.5±87.8 mL, and 69.5±16.9 minutes. The learning curve in terms of average operative time during five years decreased from 82±18.5 minutes to 57.8±5.2 minutes. Total complication rate was 10.6% including 7.9% intraoperative and 2.6% postoperative. Total complication rate decreased from 20% in 2013 to 2.2% in 2017. Most ureteral injuries were diagnosed postoperatively. Especially we observed no ureteral injury between 2015 and 2017 and there was 5.9% and 13.3% ureteral injury rate in 2014 and in 2013; respectively. Conversion rate to laparotomy was 3.3%. Conclusion: LH is a good alternative to abdominal hysterectomy wherever an advanced laparoscopic skilled surgeon can safely perform this procedure. Lower complication (especially urinary) rates can be expected with better handling of the uterus via manipulators, consideration of anatomical proximities, and always following safe dissection rules.